Repurposing the yellow fever vaccine for intratumoral immunotherapy - Aznar, Maria Angela (EMBO Mol Med, 2019)
Live 17D is widely used as a prophylactic vaccine strain for yellow fever virus that induces potent neutralizing humoral and cellular immunity against the wild‐type pathogen. 17D replicates and kills mouse and human tumor cell lines but not non‐transformed human cells. Intratumoral injections with viable 17D markedly delay transplanted tumor progression in a CD8 T‐cell‐dependent manner. In mice bearing bilateral tumors in which only one is intratumorally injected, contralateral therapeutic effects are observed consistent with more prominent CD8 T‐cell infiltrates and a treatment‐related reduction of Tregs. Additive efficacy effects were observed upon co‐treatment with intratumoral 17D and systemic anti‐CD137 and anti‐PD‐1 immunostimulatory monoclonal antibodies. Importantly, when mice were preimmunized with 17D, intratumoral 17D treatment achieved better local and distant antitumor immunity. Such beneficial effects of prevaccination are in part explained by the potentiation of CD4 and CD8 T‐cell infiltration in the treated tumor. The repurposed use of a GMP‐grade vaccine to be given via the intratumoral route in prevaccinated patients constitutes a clinically feasible and safe immunotherapy approach.